PDF Temporal Pulse Compression Using Double Cladding Polarization Maintaining Fiber Nested Mach- Zehnder Interferometer - Othafa, Ahmed; Mansour, Tahreer Safa’a (Iraqi Journal of Laser, 2022)
Abstract: Narrow laser pulses have been essential sources in optical communication system. High data rate optical communication network system demands compressed laser source with unique optical property. In this work using pulsed duration (9) ns, peak power 1.2297mW, full width half maximum (FWHM) 286 pm, and wavelength center 1546.7 nm as compression laser source. Mach Zehnder interferometer (MZI) is built by considering two ways. First, polarization maintaining fiber (PMF) with 10 cm length is used to connect between laser source and fiber brag grating analysis (FBGA). Second, Nested Mach Zehnder interferometer (NMZI) was designed by using three PMFs with 10 cm length. These three Fibers are splicing to single mode fiber (SMF-28) that has 5cm length. Both designs are etching in Hydrofluoric acid HF 40 percent concentration with three different duration time (10,20 and 30) min. Tunability of this pulsed laser source can be chained after applying different mechanical weights (0,10,50,100,250,500) g are applied to two areas across the fiber; the cross section and splicing regions. It was possible to observe, the maximum excitation of higher order modes for compression factor (FC) was found in splicing region which it is 1.02. this value is recorded under 500g that subjected to the fiber that has 10cm length with 30 min etching. In addition, the thickness cladding was 72.8 µm. also, the maximum peak power for both designs is 90.124 µw and wavelength center is 1546.817 nm.